Trends, opportunities, and challenges of artificial intelligence in elementary education - A systematic literature review - Yusuf, Furtasan Ali (Journal of Integrated Elementary Education, 2025)
This study aims to analyze the trends, opportunities, and challenges of implementing Artificial Intelligence (AI) in primary education based on a systematic literature review. The research method employed the Systematic Literature Review (SLR) approach with PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). Data collection techniques involved searching references from reputable journal databases such as Scopus, Web of Science, ERIC, Google Scholar, IEEE Xplore, Taylor & Francis Online, and Wiley Online Library, resulting in 45 studies (2016-2024) selected based on relevance to AI in primary education. The study results indicate that (1) AI trends in primary education are dominated by Augmented Reality (AR), Virtual Reality (VR), Learning Management Systems (LMS), and Adaptive Learning Systems; (2) Opportunities for AI in primary education include the development of more effective and measurable AI technology innovations and their widespread application to improve student learning outcomes; and (3) Challenges in implementing AI in primary education include technological disparities, high costs, uneven infrastructure, lack of teacher training, and insufficient technological and budget support, and student data privacy. The study concludes that AI in primary education has the potential to enhance learning quality through AR, VR, LMS, and Adaptive Learning, yet still faces challenges related to technological disparities, costs, infrastructure, and teacher training. This study offers insights for policymakers and educators to strengthen teacher competence, improve infrastructure, and ensure equitable AI access in schools.